p-Geodesic transformations and their groups in second-order tangent bundles induced by concircular transformations of bases - Zubrilin, K. M. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We investigate the flattening properties of the Lie group G_r^II of transformations of a second-order tangent bundle T^2(M) equipped with the lift ∇^II of an affine connection ∇ and the lift g^II of a metric g on the base of M induced by the Lie group G_r of concircular transformations of the base of M. The obtained results reveal certain geometric features of the induced group G_r^II within the framework of the theory of p-geodesic mappings.